Efektifitas Terapi Dingin Dan Natrium Diklofenak Topical Dalam Menghambat Oedema Pada Tikus Putih Betina Galur Wistar Pasca Induksi Karagenin - Harianto, Dicky; , Wahyuni, S.Fis.,Ftr.,M.Kes; , Umi Budi Rahayu, S.Fis.,Ftr.,M.Kes (2015)
Background: Injury is a problem that is difficult to avoid by sportsmen, both in competition and in exercise time. Prevalensi currently quite large and most of the healing is not perfect, so there is a tendency to get injured replications. Right treatment at time of the acute injury would accelerate the healing process and avoid more severe complications eg worsening of inflammation even a risk of repeated injury. There are some common treatment for the treatment of acute injuries, in the of physiotherapy is RICE is Rest (Rest), Ice (Cold Therapy), Compression (Compression), Elevation (Raising Injury Area) while ordinary people using chemical drugs which are on the market with diclofenac sodium. The Objective of Research: To determine the effectiveness of the treatment of cold and diclofenac sodium preformance inhibit edema. The Benefits of Research : to provide information about the use of cold therapy to be used as an alternative replacement for chemical drugs as inhibitors of edema. The Method of Research: This study use eksperimental pure research methods with methods three group pre and post test design. The sample selection of test animals that is based on the age of 2-3 months with body weight 180-300 grams and a female by measuring volume using a rat foot is plastimometer with parameter milliliter (ml). statistical analysis using analysis of variance was followed by a two-lane test of least significant differences (LSD). Results of The Research: Based on the statistical analysis found the effectiveness of cold therapy and sodium diclofenac respectively show a significant difference in inhibiting edema (sig <5%). Conclusion: Sodium diclofenac topical better than cold treatment in inhibiting edema.